CHARACTERISTICS OF TECTONIC EARTHQUAKE SUMATERA - Yudi Antomi (International Remote Sensing Applied Journal, 2020)
This study aims to answer the question: is there a correlation between earthquake events due to Benioff zone activity with earthquake events due to shallow local cesarean activity? Using a spatial statistical local moran, krigging, and kernel density approach to the distribution of 1973 – 2018 earthquake occurrences in the central region of Sumatra, it was found that there was a connection between earthquake events due to Benioff zone activity and earthquake events due to shallow local cesarean activity. The earthquake activity between the Mentawai Islands and the coast of West Sumatera - Bengkulu was more caused by local cesarean activity with superficial hypocenter.